A comparison of serological phenotyping and molecular genotyping for Kell, Kidd, and Duffy antigens in multi-transfused thalassemia patients - Atul Sonker; Anju Dubey; Yatendra Mohan (Asian Journal of Transfusion Science, 2023)
BACKGROUND: In multi-transfused thalassemia patients, serological phenotyping fails to test patient's actual blood group antigen profile due to the presence of donor red blood cell (RBC) in the circulation. This limitation of serological tests can be overcome by genotype determination using the polymerase chain reaction (PCR)-based methods. The aim of this study is to compare the serological phenotyping of Kell, Kidd, and Duffy blood group systems with molecular genotyping in the normal blood donors and multi-transfused thalassaemia patients. MATERIALS AND METHODS: Blood samples from 100 normal blood donors and 50 thalassemia patients were tested using standard serological techniques and PCR-based methods for Kell (K/k), Kidd (Jka/Jkb), and Duffy (Fya/Fyb) blood group systems. The results were compared for concordance. RESULTS: Genotyping and phenotyping results were 100% concordant for normal blood donors whereas those for thalassemia patients showed 24% discordance. The frequency of alloimmunization in thalassemia patients was 8%. The results of genotyping were used to provide Kell, Kidd, and Duffy matched blood for transfusion therapy to thalassemia patients. CONCLUSION: The actual antigen profile in multitransfused thalassaemia patients can be reliably determined using genotyping. This would benefit in providing better antigen matched transfusion therapy to such patients hence reducing the rate of alloimmunization.